Market Reactions to Tangible and Intangible Information - DANIEL, KENT; TITMAN, SHERIDAN (Journal of Finance, 2006)
ABSTRACT The book‐to‐market effect is often interpreted as evidence of high expected returns on stocks of “distressed” firms with poor past performance. We dispute this interpretation. We find that while a stock's future return is unrelated to the firm's past accounting‐based performance, it is strongly negatively related to the “intangible” return, the component of its past return that is orthogonal to the firm's past performance. Indeed, the book‐to‐market ratio forecasts returns because it is a good proxy for the intangible return. Also, a composite equity issuance measure, which is related to intangible returns, independently forecasts returns.